Pemberdayaan UMKM Bale Mpaq melalui Sosialisasi Pengelolaan Limbah Perikanan Menuju Zero Waste - Pawestri, Setyaning; Zuhriatika Rasyda, Riezka; Fajar Perdhana, Firman; Nofrida, Rini; Devi Ariyana, Mutia; Rahayu, Novia; Marisya Dwi Anggraini, Ines; Murad; Vrisco Harjanto; Putri Sulhana El Fiesha Balqis; Iqlima Khaerunnisa (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The global challenge of zero waste is paramount for optimizing resource use and curbing environmental pollution, aligning directly with the Sustainable Development Goals (SDGs). This concept holds particular significance within the food processing industry. Bale Mpaq, a small-scale fish processing enterprise, has demonstrated commitment to waste reduction by repurposing fish bones into fish sticks. Despite these efforts, fish waste still accounts for 30–40% of their production, presenting a substantial environmental concern if not properly addressed. In response, a community service program was initiated to bolster the expertise of Bale Mpaq's participants in sustainable fish waste management. The program will deliver comprehensive outreach and practical training, enabling participants to identify waste sources, understand their environmental ramifications, explore avenues for material recovery, and implement appropriate waste management methodologies. This initiative is designed to not only minimize environmental harm but also to elevate the quality and market competitiveness of products from small businesses. Furthermore, it will foster the development of novel, value-added products from fish waste, thereby generating new income streams and increasing productivity for Bale Mpaq.